Особенности учета объектов интеллектуальной собственности, как нематериальных активов - Аврамова, О. Е.; Пономарева, Е. Е. (НТУ "ХПИ", 2013)
The article is devoted to the accounting issues of intellectual property. Intellectual property is intangible assets of the enterprise. It is established that the recognition of an intangible asset must have the ability to bring economic benefits to the taxpayer.
Keywords: права исключительные; активы предприятия; учет бухгалтерский; выгода экономическая